HISTORIC DEVELOPMENT OF THE CHRONIC OBSTRUCTIVE PULMONARY DISEASE CLASSIFICATION - A. V. Nikitin; L. V. Vasilyeva; E. P. Karpukhina; E. M. Tolstykh (Туберкулез и болезни лёгких, 2018)
The article describes the history of the classification of chronic obstructive pulmonary disease, which leads to Global Initiative for Obstructive Lung Disease ‒ GOLD, a document describing all aspects of this disease which are currently known.